ФІСКАЛЬНИЙ МЕХАНІЗМ ПІДТРИМКИ ВИРОБНИКІВ: СУТНІСТЬ І СТРУКТУРА - Ватагович, Михайло Іванович (Науковий журнал «Світ фінансів», 2019)
Ватагович М. І. Фіскальний механізм підтримки виробників: сутність і структура. Проаналізовано наукові підходи до визначення поняття фіскального механізму підтримки виробників та розкрито теоретичні засади його структуризації. Доведено, що комбінування різних елементів зазначеного механізму на практиці здійснюється залежно від цілей державної політики на певному етапі її реалізації. Запропоновано засоби фіскального механізму підтримки виробників поділяти на дві групи: які забезпечують функціонування усього механізму та його інструментарію і які об’єднують та забез-печують використання певних груп інструментів. Ватагович М. И. Фискальный механизм поддержки производителей: сущность и структура. Проанализированы научные подходы к определению понятия фискального механизма поддержки производителей и раскрыты теоретические основы его структуризации. Доказано, что комбинирование разных элементов указанного механизма на практике осуществляется в зависимости от целей государственной политики на определенном этапе ее реализации. Предложено средства фискального механизма поддержки производителей подразделять на две группы: обеспечивающие функционирование всего механизма и его инструментария; объединяющие и обеспечивающие использование определённых групп инструментов. Vatagovych M. Fiscal mechanism for producer support: essence and structure. Introduction. In economic practice, fiscal instruments of producer support and production are widely used, and their modernization is continuous. The use of each of these tools is not a separate process, occurs in a particular environment, with the implementation of a set of interrelated and consistent actions. Consequently, there is a fiscal mechanism for the support of producers, which in the financial theory has found only a partial reflection. Purpose. The purpose of the article is to formulate its own approach to the definition of the nature and structuring of the fiscal mechanism of producer support. Results.The fiscal mechanism for producer support is a set of fiscal, tax and tax forms, tools and instruments through which the state can exert a stimulating effect on the activities of economic entities of its jurisdiction. All means of fiscal support for producers can be divided into two groups: ensuring the functioning of the whole mechanism and its tools (planning and forecasting in the fiscal sector, fiscal norms, norms and standards); combining and ensuring the use of certain groups of instruments (budget expenditures (includes and ensures the use of such instruments: budget financing of state participation in capital; budget financing of public procurement; budget subsidies and subsidies; the establishment of fiscal administrative rules and sanctions for their violation), taxation (includes and ensures the use of such instruments: the establishment of reduced rates of taxation and their change; the establishment of tax privileges and preferential tax subsystems; the introduction of tax holidays, the establishment of fiscal rules and sanctions for their violation), state loans (includes and provides the use of such instruments: state-owned preferential loans, state loan guarantees, the establishment of fiscal rules and sanctions for their violation). Conclusions.The fiscal mechanism of producer support is a multilevel system characterized by hierarchy and the existence of links between internal elements and the external environment. In addition, it is a management system, the functioning of which plays a significant role subjective factor. Therefore, an important task of financial theory is not only its research as a given, but also the design and modernization of the elemental composition, the justification for improving the functioning and use in the interests of the development of individual producers, industries and types of economic activity, society as a whole.